Effect of Audio-Visual Health Education on Knowledge Level of Elderly with Uric Acid Disease - Nurjannah; Lindra, Resti Maisa; Khassim, Said Sudi (Vocational: Journal of Educational Technology, 2025)
Gout is a common health problem among the elderly, often exacerbated by limited knowledge regarding its management and prevention. This study aims to determine the effect of audiovisual health education on the knowledge level of elderly individuals with gout. A pre-experimental design with a one-group pre-test and post-test approach was employed. The research was conducted at the Bina Sejahtera Lansia Posyandu, Palembang City, on December 7, 2024. The sample consisted of 30 elderly participants selected using purposive sampling. Data collection began with a pretest to assess baseline knowledge using a structured questionnaire. Participants then received an audiovisual health education intervention, followed by a posttest to evaluate changes in knowledge. The results showed an increase in the average knowledge score from 6.07 (pre-test) to 8.33 (post-test). Statistical analysis using the Wilcoxon test yielded a p-value of 0.000 (p<0.05), indicating a significant improvement in knowledge after the intervention. These findings imply that audiovisual health education can be an effective method to enhance disease-related knowledge among the elderly, particularly in community-based health settings. Improving knowledge is a crucial step toward empowering the elderly to manage and prevent gout more effectively.